Potential temperature inversion: Complementary approaches - Egger, Joseph; Hoinka, Klaus-Peter (Journal of the Atmospheric Sciences, 2010)
Given the distribution of one atmospheric variable, that of nearly all others can be derived in balanced flow. In particular, potential vorticity inversion (PVI) selects PV to derive pressure, winds and potential temperature θ. Potential temperature inversion (θI) starts from available θ-fields to derive pressure, winds and PV. While PVI has been applied extensively, θI has hardly been used as a research tool although the related technical steps are well known and simpler than those needed in PVI. Two idealized examples of θI and PVI are compared. ERA analyses are used to determine typical anomalies of PV and of θ in the North Atlantic stormtrack region. Statistical forms of PVI and θI are applied to these anomalies. The inversions are equivalent but the results of θI are generally easier to understand than those of PVI. The issues of attribution and piecewise inversion are discussed.